Coconut Oil: A Heart Healthy Fat? - Wendy M. Gans; Gail P. Kauwell (EDIS)
There are many claims about the health benefits of coconut oil. But what is the evidence behind these health claims? Read this five-page fact sheet to learn more about coconut oil and how it might affect heart health. Written by Wendy M. Gans and Gail P.A. Kauwell and published by the Food Science and Human Nutrition department.http://edis.ifas.ufl.edu/fs289